2021
DOI: 10.5339/qmj.2021.26
|View full text |Cite
|
Sign up to set email alerts
|

The Arabic version of the sleep hygiene index: Linguistic validation and cultural adaptation among University students in Qatar

Abstract: Introduction: Sleep is necessary for maintaining adequate health and well-being. However, several behavioral and environmental factors, known as sleep hygiene, could affect sleep quality, contributing to the development of insomnia. Instruments to measure sleep hygiene such as the sleep hygiene index (SHI) have been developed, but only a few are available in the Arabic language. Therefore, this study was designed to translate and culturally adapt the SHI from English to Arabic. Methods: The SHI was translated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
2
3
1
Order By: Relevance
“…In the presentation article, the SHI-13 showed acceptable internal consistency, Cronbach’s alpha of .66, high test-retest stability, r of .71 (p<.01), and acceptable nomological validity, with a modest high correlation with the Epworth Sleepiness Scale (ESS), r of .24 (p<.01) and adequate correlation with the Pittsburgh Sleep Quality Index, r of .48 (Mastin et al, 2006). These characteristics have been corroborated in other studies with the participation of university students, particularly internal consistency values, Cronbach’s alpha, or McDonald’s omega, less than .70 (Ali et al, 2021; Kaur & Singh, 2017; Seun-Fadipe et al, 2018; Tang et al, 2021). Generally, internal consistency values greater than .70 are recommended (Campo-Arias & Oviedo, 2008; Kezsei et al, 2010).…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…In the presentation article, the SHI-13 showed acceptable internal consistency, Cronbach’s alpha of .66, high test-retest stability, r of .71 (p<.01), and acceptable nomological validity, with a modest high correlation with the Epworth Sleepiness Scale (ESS), r of .24 (p<.01) and adequate correlation with the Pittsburgh Sleep Quality Index, r of .48 (Mastin et al, 2006). These characteristics have been corroborated in other studies with the participation of university students, particularly internal consistency values, Cronbach’s alpha, or McDonald’s omega, less than .70 (Ali et al, 2021; Kaur & Singh, 2017; Seun-Fadipe et al, 2018; Tang et al, 2021). Generally, internal consistency values greater than .70 are recommended (Campo-Arias & Oviedo, 2008; Kezsei et al, 2010).…”
Section: Introductionsupporting
confidence: 74%
“…Likewise, nomological validity was limited because only factor 2 (cognitive activation) showed significant correlations, more excellent than .30, with the Depression, Anxiety, and Stress Scale (DASS-21) and the Pittsburgh Sleep Quality Index (PSQI). Consequently, the dimensions of the HSI-10 showed better internal consistency than that observed in other studies for the global SHI-13 (Ali et al, 2021; Kaur & Singh, 2017; Mastin et al, 2006; Seun-Fadipe et al, 2018; Tang et al, 2021).…”
Section: Introductioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The Arabic SHI has moderate internal consistency reliability with a Cronbach’s alpha of 0.589. 43 , 44 …”
Section: Methodsmentioning
confidence: 99%
“…Evidence has shown that students' sleep hygiene practices are inadequate and worse than those of healthy adults. Commonly reported unhealthy sleep hygiene practices by university students are found to be irregular bedtimes, napping, use of stimulants, and use of electronic devices before bed (Ali et al, 2023). Psychological health problems among these students are also prevalent.…”
Section: Introductionmentioning
confidence: 99%